2020
DOI: 10.1186/s12891-020-3052-8
|View full text |Cite
|
Sign up to set email alerts
|

Are viruses associated with disc herniation? A clinical case series

Abstract: Background: There is some limited evidence for the presence of viruses in herniated disc material including a previous case series that claimed to provide "unequivocal evidence of the presence of herpes virus DNA in intervertebral disc specimens of patients with lumbar disc herniation suggesting the potential role of herpes viruses as a contributing factor to the pathogenesis of degenerative disc disease". This study has not been replicated. The objective of our study was to determine if viruses were present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Studies on viral infections of the intervertebral disc are rare [10,37,38]. Alpantaki et al [10] reported a prevalence of positive PCR tests of 56.25% for HSV-1 and 37.5% for CMV in 16 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on viral infections of the intervertebral disc are rare [10,37,38]. Alpantaki et al [10] reported a prevalence of positive PCR tests of 56.25% for HSV-1 and 37.5% for CMV in 16 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alpantaki et al [10] reported a prevalence of positive PCR tests of 56.25% for HSV-1 and 37.5% for CMV in 16 patients. Walker et al [38] investigated herniated disc tissue of 15 patients for herpesvirus DNA and did not detect any viral pathogens. In our sample, we found no evidence of any infection of the intervertebral discs by HSV-1, HSV-2, or CMV.…”
Section: Discussionmentioning
confidence: 99%
“…The other gene sets that were found significantly enriched among the differentially expressed genes across all STIR variables were pathways related to defense response to virus and mitochondrial metabolism. The involvement of viruses in the degeneration and herniation of discs have been suggested, but studies show inconclusive results 71 . However, the genes underlying the defence to virus pathway have rather broad immune and inflammatory functions also occurring without a viral trigger.…”
Section: Discussionmentioning
confidence: 99%